2020
DOI: 10.1016/j.annonc.2020.01.065
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular correlates of PD-L1 expression in patients with lung adenocarcinomas

Abstract: Background: Programmed death-ligand 1 (PD-L1) expression is the only FDA-approved biomarker for immune checkpoint inhibitors (ICIs) in patients with lung adenocarcinoma, but sensitivity is modest. Understanding the impact of molecular phenotype, clinical characteristics, and tumor features on PD-L1 expression is largely unknown and may improve prediction of response to ICI. Patients and methods: We evaluated patients with lung adenocarcinoma for whom PD-L1 testing and targeted nextgeneration sequencing (using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
170
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(209 citation statements)
references
References 50 publications
18
170
4
Order By: Relevance
“…Later, the mechanism causing KRAS to upregulate PD-L1 was shown to be through increases in PD-L1 mRNA stability via modulation of the AU-rich element-binding protein tristetraprolin (TTP), mediated by downstream MEK signalling 62 . The evaluation of patients with LAC showed a strong association between KRAS mutations and high PD-L1 expression 63 , which is contrasting to reports in CRC 64 . Canon and colleagues described the potential of combining the novel KRAS G12C inhibitor AMG 510 with immune-checkpoint inhibitors, and showed that the combination of AMG 510 with anti-PD-1 blockade induced tumour cell killing, and improved the sensitivity of the TME to immunotherapy 65 .…”
Section: Kras-induced Immune Modulationcontrasting
confidence: 91%
“…Later, the mechanism causing KRAS to upregulate PD-L1 was shown to be through increases in PD-L1 mRNA stability via modulation of the AU-rich element-binding protein tristetraprolin (TTP), mediated by downstream MEK signalling 62 . The evaluation of patients with LAC showed a strong association between KRAS mutations and high PD-L1 expression 63 , which is contrasting to reports in CRC 64 . Canon and colleagues described the potential of combining the novel KRAS G12C inhibitor AMG 510 with immune-checkpoint inhibitors, and showed that the combination of AMG 510 with anti-PD-1 blockade induced tumour cell killing, and improved the sensitivity of the TME to immunotherapy 65 .…”
Section: Kras-induced Immune Modulationcontrasting
confidence: 91%
“…the expression of PD-L1 seems to be lower in primary tumor samples than in metastases. This indicates that an advanced disease may be more likely to express PD-L1 than an earlier stage disease [22]. the extent of PD-L1 expression in metastases varies modestly by anatomic site.…”
Section: Introductionmentioning
confidence: 94%
“…Tumor-cell-intrinsic oncogenic pathways including STK11/LKB1 and KEAP1 are associated with a "cold", non-T cell-inflamed TME, thus significantly impairing clinical responses to ICI treatment [22,63,64,161,162]. The inactivation of STK 11 increases production of G-CSF, CXCL7 and IL-6, which recruit tumor-associated neutrophils that in turn increase T-cell dysfunction via arginase A and IL-10 release [22,162]. Along with that, this genomic alteration has been identified as a major driver of de-novo resistance to PD-1 axis resistance in KRAS-positive lung adenocarcinoma [63].…”
Section: Stk11/keap1mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the predictive importance of KRAS mutations for the efficacy of immune checkpoint inhibitors have not uniformly provided positive results. Mutant KRAS was associated with increases in tumor infiltrating lymphocytes, PD-L1 expression and tumor mutational burden [ 182 , 183 ]. However, while Gianoncelli et al observed no significant differences between KRAS + and non- KRAS NSCLC patients in terms of progression-free or overall survival [ 184 ], Kauffmann-Guerrero et al reported a positive outcome for KRAS mutations in response to immune checkpoint inhibitors [ 185 ].…”
Section: New Optimism For Targeting Kras Mutatimentioning
confidence: 99%